From the Biennale to Oblivion: The Impact of Social Changes on the Preservation of Modernist Architecture Identity in Montenegro Through Case Studies of the Kolašin Memorial House, the House of Revolution in Nikšić, and the Hotel Fjord in Kotor - Nikolić, Viktorija; Marovic, Tamara (Arhitektura i urbanizam, 2025)
This research examines modernist architecture in Montenegro, with a particular focus on three representative buildings showcased at the 14th Venice Architecture Biennale in 2014. The aim is to explore the challenges and opportunities for preserving these structures within the context of contemporary social, political, and economic transformations. The methodological approach is based on case studies and qualitative research techniques, incorporating a comparative analysis that traces the evolution and transformation of the Kolašin Memorial House, the House of Revolution in Nikšić, and the Fjord Hotel in Kotor over the past decade, following their presentation at the Venice exhibition. The evaluation was conducted through the analysis of three key parameters: architectural, functional, and social identity. The research results indicate significant degradation and neglect of these structures, leading to the loss of their original purpose and identity. These processes stem primarily from socio-political changes following the dissolution of Yugoslavia. Although the Kolašin Memorial House has been partially preserved, the Hotel Fjord has been completely demolished, while the House of Revolution has become the target of various investment projects and commercialization, with new developments functioning as independent spatial units that disregard the architectural authenticity and integrity of the original structure. The study concludes by emphasizing the urgent need for institutional interventions, legal protection, and clearly defined guidelines for preserving these buildings. Their cultural and architectural significance must be adequately recognized and preserved, as modernist architecture plays a critical role in safeguarding and transmitting Montenegro’s cultural identity to future generations. In the absence of these measures, there is a serious risk of irreversibly losing a significant part of the nation’s architectural heritage.
Keywords: Architecture in Montenegro; architectural heritage; Memorial House Kolašin; House of Revolution Nikšić; Fjord Hotel Kotor